Microscopic Evaluation Of The Natural Coral (Porties spp.) Post-implantation In Sheep Femur. - Fadilah, A.; Zuki, A.B.; Loqman, M.Y.; Saad, M Zamri; Al-Salihi, K A; Norimah, Y.; Asnah, H. (2004)
Bone defects resulting from congenital defects, tumor or trauma are conventionally repaired using bone graft. Allogenic and xenogenic bone grafts are used as alternatives but several problems are generally associated with them such as virus transfer, considerable care, high cost and regular immuna-defensive reaction.